ANALYSIS OF AIRCRAFT DELAYS IN FIR WARSAW IN THE CONTEXT OF RADIONAVIGATION SYSTEMS - Magda MROZIK (Scientific Journal of Silesian University of Technology. Series Transport)
The paper contains an analysis of the causes of aircraft delays at the main airports in Poland. Due to the fact that for several years there has been a large increase in the volume of air traffic, generates operational and organisational problems related to aircraft servicing, both at the airport and in the air. Due to the PBN STAR procedure, it is possible not only to make more efficient use of the airspace, such as route layout, reduction of flight time by at least 2 min, reduction of separation but also to reduce the amount of harmful substances produced by the aircraft. When performing RNAV GNSS air operations, an aircraft saves approximately 275 kg of fuel per flight, which has a significant impact on environmental protection.